Measurement of Supply Chain Management Performance Using SCOR Model - Ayi Tejaningrum (AIBPM Publisher, 2022)
This research was conducted in the chicken egg distributor industry, which has problems in the management of the supply chain, especially in the flow of materials, information, and finance, which is related to the decline in the company's performance, especially in the aspects of consumer satisfaction and congestion in the financial flow. This study aims to look at the flexibility of the supply chain from upstream to downstream, especially concerning distribution aspects to get to consumers, looking for improved solutions to improve organizational performance. Research Case studies on Industries engaged in the distribution of chicken eggs. The research method is a survey with a case study approach. Supply chain performance obtained value for Perfect Order Fulfillment (POF) of 70.8%, meaning that the company has not perfectly achieved supply chain performance, with Supply Chain Responsiveness of 3 days and Supply Chain Cost of 54%. This condition indicates that the average performance of the supply is still in the category of less good. This study only examined the supply chain between internal supply and downstream without involving upstream due to data and information limitations. The research includes cost elements as part of supply chain performance, not only analyzing aspects of the fulfillment of materials and information. Keywords: Corporate Performance, Logistic, Score Model, Supply Chain